2012
DOI: 10.1002/hbm.22102
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical flutter stimulation induces a lasting response in the sensorimotor cortex as revealed with BOLD fMRI

Abstract: It has been recently shown that 20 min of mechanical flutter stimulation induces lasting motor cortical excitability changes, as assessed by transcranial magnetic stimulation in relaxed hand muscles. The present functional magnetic resonance imaging (fMRI) study aims to examine if such neuromodulatory changes are reflected in the BOLD signal during a motor test. Therefore, two groups were recruited: one group receiving whole-hand flutter stimulation with a frequency of 25 Hz (FSTIM group, n = 22) and a second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 58 publications
2
21
1
Order By: Relevance
“…None of the studies investigating changes in the BOLD signal strength could find differences in the activation of S2 (Christova et al, 2012;Golaszewski et al, 2004;Wu et al, 2005), which is in contrast to the findings on localization of activation peaks and activated clusters (Hodzic et al, 2004;Pleger et al, 2003). It was proposed that the lack of effect in studies treating BOLD signal changes relates to the fact that S2 is less somatotopically organized and that there is more overlap between representations of different body sites.…”
Section: Different Stimulation Protocolscontrasting
confidence: 52%
See 4 more Smart Citations
“…None of the studies investigating changes in the BOLD signal strength could find differences in the activation of S2 (Christova et al, 2012;Golaszewski et al, 2004;Wu et al, 2005), which is in contrast to the findings on localization of activation peaks and activated clusters (Hodzic et al, 2004;Pleger et al, 2003). It was proposed that the lack of effect in studies treating BOLD signal changes relates to the fact that S2 is less somatotopically organized and that there is more overlap between representations of different body sites.…”
Section: Different Stimulation Protocolscontrasting
confidence: 52%
“…RTS increased activity in M1 as well as S1 was found through fMRI (Christova et al, 2012;Wu et al, 2005) and MEG (Golaszewski et al, 2010;Golaszewski et al, 2012;Kowalewski et al, 2012). Indeed, Wu et al found an even bigger increase of activation in M1 than in S1 (Wu, van Gelderen et al 2005).…”
Section: Effects Of Rts On the Motor Levelmentioning
confidence: 96%
See 3 more Smart Citations